Red Yeast Rice and Optimal Fermentation Periods Improve the Quality of Esan Fermented Fish Sausage - Somsamorn Gawborisut; Suprawee Muengkratok (International Journal of Food Science)
Esan fermented fish sausage (EFFS) has an unappealing off-white color. The incorporation of an appropriate amount of red yeast rice (RYR) and the selection of an optimal fermentation period may yield visually appealing, high-quality sausages. This study is aimed at investigating the effects of different RYR levels (0, 0.35, and 0.7%) and fermentation periods (0, 2, 4, and 6 days) on the quality parameters of EFFS. The following parameters were examined for raw EFFS: CIE color values (L∗, a∗, and b∗), microbial analyses (total viable count, lactic acid bacteria, and yeast and mold counts), titratable acidity (TA), pH, weight loss, cooking loss, texture profile analysis (TPA), and sensory evaluation (color, odor, hand-feel texture, overall acceptability, and overall preference ranking). The quality parameters of the cooked EFFS were CIE color values and sensory evaluation (color, odor, mouthfeel, texture, flavor, overall acceptability, and overall preference ranking). The results showed that 0.35 and 0.7% RYR increased the a∗ (red/green) values of raw and cooked EFFS but decreased the L∗ (lightness) and b∗ (yellow/blue) values. These RYR levels significantly improved the sensory color, overall acceptability, and overall preference ranking of the raw and cooked EFFSs. However, no statistical differences were observed between the effects of 0.35 and 0.7% RYR. RYR levels did not affect the microbial analyses, TA, pH, weight loss, cooking loss, or TPA. Moreover, they had no effect on the odor and hand-feel texture of raw EFFS, or the odor, mouthfeel texture, or flavor of cooked EFFS. Therefore, RYR supplementation improved the color quality of the EFFSs without altering the other quality parameters, with 0.35% RYR deemed optimal. Moreover, the fermentation period significantly influenced most quality parameters, except CIE color values and sensory color perception of raw and cooked EFFSs. Most sensory parameters improved by day 2, remained unchanged until day 4, and then deteriorated on day 6.